Zwitterionic modification of ultrasmall iron oxide nanoparticles for reduced protein corona formation - Pombo García, Karina; Comba, Peter (ChemPlusChem, 2017)
Polyacrylic-acid-coated ultra-small super-paramagnetic iron oxide nanoparticles were surface-modified with low-molecular-weight sulfobetaines or 3-(diethylamino)propylamine in order to generate nanoparticles with zwitterionic character (ZW-NPs). The ZW-NPs proved highly resistant to serum protein corona formation in vitro, as revealed by atomic force microscopy, SDS-PAGE and proteomics analysis, and exhibited low cytotoxicity towards A431 and HEK293 cells. The presence of unreacted carboxylic acid groups enabled additional functionalization with fluorescent (Cy5) and radioactive [64Cu-dmptacn; dmptacn=1,4-bis(2-pyridinylmethyl)-1,4,7-triazacyclononane] moieties. Overall, the ZW-NPs represent promising platforms for the development of new multimodal diagnostic/therapeutic agents possessing “stealth” properties.
First published: 06 March 2017
Gesehen am 15.06.2018